Agricultura familiar, organização espacial e a expansão da soja no município de Espumoso, RS - Fruet, Zuleide (2018)
Geographic space is organized by the relations established between society and nature, and economic, political, cultural and technological factors modify the environment in which they are inserted. However, when the society / nature relationship changes it causes a spatial reorganization. The agricultural sector has been undergoing a productive restructuring, in which it modifies the agrarian space. It can be inferred that agrarian space is organized and reorganized insofar as it is influenced by new economic agents, which reflects in the agrarian sector, through the emergence and insertion of different cultures, as well as by the modernization process of agriculture. In this way, the research focuses on the territorial unit of Espumoso, Rio Grande do Sul. This has its economic matrix linked to the primary sector, where in the first moment, livestock was the main activity, however, over the years, the primary sector underwent several transformations, mainly due to the emergence of other crops, such as the soybean crop and also the process of modernization of agriculture reflected in the downsizing of the productive segment. In this sense, the main objective of the research is to analyze the socio-spatial organizations resulting from the expansion of soybean culture in Sparkling and its impacts on family agriculture. Specifically the objectives are: (a) to verify the causes that influenced the process of introduction of the soybean crop into Sparkling; (b) to analyze the impacts of soybean production on family agriculture production units; (c) understand the factors that promote agricultural diversification in the rural area of the municipality. Methodologically, the research was structured in stages. Initially the deepening of the theoretical matrix was carried out, rescuing the main guiding concepts of the research, later applied the questionnaires and the interpretation and tabulation of the results. However, it can be observed that in Sparkling soybean cultivation is present in the family units in a predominant area, while the other cultures are then practiced in smaller areas, with food production coming from family farming, that is, is exploited in small areas of land with the use of family labor. Therefore, diversification by family farmers presents several favorable condiments such as the optimization of the area, occupation of family labor, diversification of income throughout the year, among others. Thus, agricultural diversification has the main advantage of reducing the economic risk of family farmers.